Massive ureterocele leading to urinary retention in a male neonate: A rare presentation and successful management - Rafael Nascimento Vilares; Manuela Horta; Afonso da Silva Alves Bento; Francisco Tibor Dénes; Roberto Iglesias Lopes (Urology Case Reports)
Ureterocele is a rare congenital anomaly characterized by the dilation of the distal ureter and its protrusion into the bladder, often related with duplex collecting renal system, leading to urinary obstruction.While it commonly occurs in females, this case report presents the rare presentation of a massive ureterocele in a 2-day-old male neonate, causing urinary retention. A diagnostic workup revealed bilateral hydronephrosis and a massive ureterocele. Surgical intervention with endoscopic decompression of the ureterocele successfully alleviated the obstruction.At one year follow-up, patient was completely asymptomatic and serial follow-up ultrasonography demonstrated resolution of hydronephrosis, highlighting the successful management.